Development of E-Modules Based on Google Workspace For Education in Improving Teachers' Digital Literacy Competencies - Desy Putri Sahara; Andi Nurhartina; Marlin Katulung (Global Education Journal, 2025)
Digital literacy competence of teachers refers to their ability to understand, use, and leverage digital technology for teaching and daily work activities. It includes the skills to locate, evaluate, create, and communicate information using various digital tools. This study aims to develop a training e-module on using Google Workspace for Education to strengthen teachers' digital literacy competence. The research employed a Research and Development (R&D) approach and was conducted at SD PGRI Serui. The product development followed the ADDIE framework: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were the teachers at SD PGRI Serui. The outcome of the study is a training e-module titled “Google Workspace for Education Application.” Expert reviews showed the module was rated very good, with average scores of 98.64%, 84.20%, and 80.00%. The module was declared valid and suitable for field testing. In individual and small group trials, the module received high practicality ratings of 85.00% and 89.00%. A large group trial revealed positive participant responses to 31 statements covering five key module criteria. Eighteen statements were rated “strongly agree” and thirteen “agree.” Thus, the module is considered good, engaging, and suitable for use in face-to-face or independent learning.